2018
DOI: 10.14349/sumapsi.2018.v25.n1.1
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Self-Curiosity Attitude-Interest Scale in Colombia

Abstract: This paper presents a theoretical review of the psychological construct of human curiosity and the Colombian version of the Self-Curiosity Attitude-Interest Scale. This is a two-factor self-report scale that assesses the attitude and the interest that people have to explore their own inner world. Two paired samples for gender, age and working class of Colombian (n = 170) and Italian (n = 195) participants (N = 365) were included in the study. Confirmatory Factor Analysis revealed a good fit of the data to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Adopting the person-centered approach highlighted some cultural differences in the measurement of self-curiosity that were not previously found. Indeed, beside partial scalar invariance found also in previous cross-country comparisons (Durosini et al, 2018;Aschieri et al, 2021), also partial metric invariance was found. This suggests that the meaning of ASC is more related to the choice of friends for the flexible individualists and rules-based competitors than for the consensus-oriented egalitarians.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Adopting the person-centered approach highlighted some cultural differences in the measurement of self-curiosity that were not previously found. Indeed, beside partial scalar invariance found also in previous cross-country comparisons (Durosini et al, 2018;Aschieri et al, 2021), also partial metric invariance was found. This suggests that the meaning of ASC is more related to the choice of friends for the flexible individualists and rules-based competitors than for the consensus-oriented egalitarians.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies found full metric invariance, but a lack of scalar invariance (Durosini et al, 2018;Aschieri et al, 2021). The lack of scalar invariance affects the final score, so it seemed that people belonging to different countries could obtain different levels of self-curiosity due to differences in the measurement of the construct.…”
Section: Introductionmentioning
confidence: 96%
“…The SCAI Scale explores curiosity about self through two factors: Attitude toward Self-Curiosity, (the individuals’ attitude to explore the personal inner world) and Interest in Increasing Knowledge of Self (the individuals’ interest in new aspects of their own selves). This instrument showed a good internal validity in Italian sample (Aschieri & Durosini, 2015: α = .65; Aschieri et al., 2016: α = .72; Durosini et al., 2018: α = .62; for more information, see Aschieri et al., 2020). In the present study, the scale revealed a Cronbach's alpha coefficients equal to .702 for the total scale ( Attitude toward Self-Curiosity: α = .748; Interest in Increasing Knowledge of Self: α = .642).…”
Section: Methodsmentioning
confidence: 93%